Dysregulated proteostasis network in neuronal diseases - Tseng, Ching-San; Chao, Yu-Wen; Liu, Yi-Hsiang; Huang, Yi-Shuian; Chao, Hsu-Wen (Frontiers in Cell and Developmental Biology, 2023)
Long-term maintenance of synaptic connections is important for brain function, which depends on varying proteostatic regulations to govern the functional integrity of neuronal proteomes. Proteostasis supports an interconnection of pathways that regulates the fate of proteins from synthesis to degradation. Defects in proteostatic signaling are associated with age-related functional decline and neurodegenerative diseases. Recent studies have advanced our knowledge of how cells have evolved distinct mechanisms to safely control protein homeostasis during synthesis, folding, and degradation, and in different subcellular organelles and compartments. Neurodegeneration occurs when these protein quality controls are compromised by accumulated pathogenic proteins or aging to an irreversible state. Consequently, several therapeutic strategies, such as targeting the unfolded protein response and autophagy pathways, have been developed to reduce the burden of misfolded proteins and proved useful in animal models. Here, we present a brief overview of the molecular mechanisms involved in maintaining proteostatic networks, along with some examples linking dysregulated proteostasis to neuronal diseases.